Method for producing vehicular window glass with resin component, and vehicular window glass with resin component

By using infrared irradiation to cure a local portion of the adhesive, the method simplifies and automates the temporary fixing of components to vehicle window glass, reducing the need for additional materials and labor.

JP2025010680APending Publication Date: 2025-01-23AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023112799
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

Existing methods for temporarily fixing components to vehicle window glass require additional materials and labor, such as double-sided tape, which are time-consuming and difficult to automate.

Method used

A method involving the use of a single adhesive for both temporary and permanent fixing, where a local portion of the adhesive is cured using infrared irradiation to quickly secure components to the glass, followed by a secondary curing process to ensure permanent adhesion.

Benefits of technology

This approach simplifies the temporary fixing process by eliminating the need for additional materials and labor, allowing for automation and reducing the time required for component attachment to vehicle window glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010680000001_ABST
    Figure 2025010680000001_ABST
Patent Text Reader

Abstract

To provide a method for producing vehicular window glass with resin components, which enables simpler temporary fastening of components.SOLUTION: The present invention provides a method for producing a vehicular window glass with resin component, including a placement step for placing a resin component onto vehicular window glass through an adhesive, and a first curing step for performing the topical application of infrared rays toward the non-adhesive face of the resin component to cure the topical portion of the adhesive.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a window glass for a vehicle with a resin part, and a window glass for a vehicle with a resin part. [Background technology]

[0002] There is known a structure in which components such as a mirror base and a bracket are bonded to a vehicle window glass with an adhesive. In manufacturing such a vehicle window glass with a component, an adhesive is applied to the bonding surface of the component, the component is attached to the vehicle window glass, and the adhesive is then cured to bond the component to the vehicle window glass.

[0003] Many of the adhesives normally used for the above-mentioned bonding require time to harden. Therefore, after the parts are attached to the vehicle window glass, they are often temporarily fixed so that the relative positions of the parts and the vehicle window glass do not shift even if a load such as vibration is applied. Although double-sided tape is well known as a means for temporary fixing, the use of a different type of adhesive that has a short hardening time other than the original adhesive is also being considered (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2022-7591 Summary of the Invention [Problem to be solved by the invention]

[0005] The above-mentioned double-sided tape or other adhesive is a material that is used in addition to the adhesive originally used. In addition, such double-sided tape or other adhesive needs to be attached or applied using a different method, so it takes time and effort to apply or attach the double-sided tape or other adhesive in addition to the application process of the adhesive originally used. Therefore, there is a demand for a simpler temporary fixing technology that reduces the number of materials and the time and effort required.

[0006] In view of the above, an object of one aspect of the present invention is to provide a technique that can more easily temporarily fasten a resin part in a manufacturing method of a vehicle window glass with the resin part. [Means for solving the problem]

[0007] In order to solve the above problems, a manufacturing method for a vehicle window glass with a resin part according to one embodiment of the present invention includes an arrangement step of arranging a resin part on the vehicle window glass via an adhesive, and a first curing step of locally irradiating infrared rays toward a non-adhesive surface of the resin part to cure a local portion of the adhesive. Effect of the Invention

[0008] According to one aspect of the present invention, in a manufacturing method of a vehicle window glass with a resin part, the part can be temporarily fixed more easily. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a diagram showing an example of a vehicle window glass with a component manufactured according to an embodiment. [Diagram 2] FIG. 2 is an enlarged view of a cross section taken along line II in FIG. [Diagram 3] FIG. 2 is a flow diagram of an example of a manufacturing method according to one embodiment. [Figure 4] 1 is a diagram showing a process of a manufacturing example of a component-equipped vehicle window glass according to an embodiment. FIG. [Diagram 5] 1 is a diagram showing a process of a manufacturing example of a component-equipped vehicle window glass according to an embodiment. FIG. [Figure 6] FIG. 6 is an enlarged cross-sectional view taken along line II-II of FIG. 5. [Figure 7] 1 is a diagram showing a process of a manufacturing example of a component-equipped vehicle window glass according to an embodiment. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the same or corresponding components are denoted by the same reference numerals, and the description thereof may be omitted.

[0011] FIG. 1 is a view of an example of a vehicle window glass 1 with a component manufactured according to an embodiment, as viewed from the vehicle inner surface side. FIG. 2 is a partially enlarged view of a cross section taken along line II in FIG. 1. As shown in FIGS. 1 and 2, a component 30 is adhered to a main surface of a vehicle window glass 10, and an adhesive 20 is used for the adhesion. In the example shown in FIGS. 1 and 2, the component 30 is a resin bracket, and the resin bracket is adhered to the upper part of the vehicle inner surface of the vehicle window glass 10, near the center in the left-right direction (FIG. 1). The component 30 may be a metal bracket. Also, the vehicle window glass 10 in FIG. 1 is a windshield, but the vehicle window glass in this embodiment may be a rear glass, a side glass, a roof glass, or the like.

[0012] As shown in Figs. 1 and 2, a shielding layer 50 is formed on the periphery of the vehicle window glass 10. The shielding layer 50 is also called a black ceramic layer. The configuration of the shielding layer 50 is not particularly limited, but it is preferable that the shielding layer 50 is a layer formed by applying and firing a ceramic paste (glass paste) having a black, gray or dark brown color. The shielding layer 50 has a function of protecting a sealant or the like for mounting and holding the vehicle window glass 10 on the vehicle body in the vehicle from ultraviolet rays and the like. The shielding layer 50 may be a layer formed by applying an organic ink or an inorganic ink. In the example of Figs. 1 and 2, the component 30 is directly bonded to the shielding layer 50 of the vehicle window glass 10 via an adhesive 20.

[0013] The vehicle window glass 10 used in this embodiment may be a glass plate such as soda lime silicate glass, aluminosilicate glass, borate glass, lithium aluminosilicate glass, or borosilicate glass. The method of forming the glass plate is not particularly limited, but glass formed by the float method is preferable. The glass plate may be unreinforced, or may be tempered glass that has been subjected to air-cooling tempering or chemical tempering treatment. Unreinforced glass is formed by forming molten glass into a plate shape and slowly cooling it. Tempered glass is formed by forming a compressive stress layer on the surface of unreinforced glass. When the tempered glass is air-cooled tempered glass, the glass surface may be strengthened by rapidly cooling a heated glass plate from a temperature near the softening point, and compressive stress is generated on the glass surface due to the temperature difference between the glass surface and the inside of the glass. On the other hand, when the tempered glass is chemically tempered glass, compressive stress may be generated on the glass surface by an ion exchange method or the like, thereby strengthening the glass surface. In addition, the vehicle window glass is preferably transparent, but may be colored glass to an extent that does not impair transparency. The shape of the glass is not particularly limited to a rectangular shape, and may be processed into various shapes. The glass plate used for the vehicle window glass may be bent and curved. Gravity forming, press forming, or the like is used for bending. When the vehicle window glass 10 according to this embodiment is for an automobile, it may be a compound curved glass curved in the front-rear direction and the up-down direction of the automobile, or a single curved glass curved only in the front-rear direction or the up-down direction. The radius of curvature of the window glass may be 200 mm or more and 300,000 mm or less.

[0014] The vehicle window glass 10 may be a single sheet of glass or may be laminated glass (FIG. 2). Laminated glass is glass formed by bonding together a plurality of glass sheets 11, 12 with an interlayer film 15 interposed therebetween. The glass sheets used in the laminated glass are also made of the above-mentioned glass.

[0015] In the laminated glass, the material of the interlayer film 15 (FIG. 2) disposed between the glass sheets 11 and 12 is not particularly limited, but is preferably a thermoplastic resin. Specific examples of the material of the interlayer film include conventionally used thermoplastic resins such as plasticized polyvinyl acetal resins, plasticized polyvinyl chloride resins, saturated polyester resins, plasticized saturated polyester resins, polyurethane resins, plasticized polyurethane resins, ethylene-vinyl acetate copolymer resins, ethylene-ethyl acrylate copolymer resins, cycloolefin polymer resins, and ionomer resins. In addition, a resin composition containing a modified block copolymer hydrogenated product described in Japanese Patent No. 6065221 can also be preferably used. Among these, a plasticized polyvinyl acetal resin is preferably used because it has an excellent balance of various performances such as transparency, weather resistance, strength, adhesive strength, penetration resistance, impact energy absorption, moisture resistance, heat insulation, and sound insulation. The above thermoplastic resins may be used alone or in combination of two or more. The term "plasticized" in the plasticized polyvinyl acetal resin means that the resin is plasticized by adding a plasticizer. The same applies to other plasticized resins.

[0016] The intermediate film 15 may be a resin that does not contain a plasticizer, such as an ethylene-vinyl acetate copolymer resin. Examples of the polyvinyl acetal resin include polyvinyl formal resin obtained by reacting polyvinyl alcohol (PVA) with formaldehyde, polyvinyl acetal resin in the narrow sense obtained by reacting PVA with acetaldehyde, and polyvinyl butyral resin (PVB) obtained by reacting PVA with n-butylaldehyde. In particular, PVB is a suitable material because it has an excellent balance of various properties such as transparency, weather resistance, strength, adhesive strength, penetration resistance, impact energy absorption, moisture resistance, heat insulation, and sound insulation. The above resins may be used alone or in combination of two or more kinds.

[0017] In the case of laminated glass, the thickness of the entire vehicle window glass (including the thickness of the interlayer film) may be 2.3 mm or more and 8.0 mm or less. The thickness of each of the multiple glass sheets constituting the laminated glass may be 0.5 mm or more and 3.5 mm or less. The thicknesses of the multiple glass sheets may be the same or different. The thickness of the glass sheet on the vehicle interior side may be 0.5 mm or more and 2.3 mm or less.

[0018] The resin part 30 is not particularly limited as long as it is a part that can be attached to any location on the main surface of the vehicle window glass 10. The part 30 may be a mirror base for mounting an inner mirror, a bracket for mounting a sensor, a molding, a protector, a pin, a clip, a holder, a hinge, or the like.

[0019] The resin part 30 may be a part entirely made of resin, such as a resin molded body, or a molded body made of a material other than resin, the surface of which is partially or entirely covered with resin. In this specification, the resin part 30 may be any part that contains resin at least on its surface.

[0020] The resin material used for the resin part 30 may be a curable resin or a thermoplastic resin. Examples of the resin include polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), polyolefins such as polyethylene (PE) and polypropylene (PP), polycarbonate (PC), polyamides (PA) such as nylon 6 and nylon 6,6, high heat-resistant polyamides based on terephthalic acid or isophthalic acid (PA6T, PA6I, PA6T / 6I, etc.), polyimide (PI), polyetherimide (PEI), acrylonitrile-butadiene-styrene (ABS), polyacetal (POM), polyvinyl chloride (PVC), and epoxy (EP). When the resin part 30 is a part in which the surface of a molded body made of a material other than resin is coated with resin, the material of the molded body may be a metal, such as aluminum, zinc, iron, or stainless steel. In this case, the metal material may be a simple metal made of one type of metal element or an alloy.

[0021] In this embodiment, the adhesive 20 is not particularly limited as long as it is an adhesive that can be used to bond the window glass 10 and the component 30, and may be an epoxy-based, urethane-based, silicone-based, modified silicone-based, melamine-based, phenol-based, acrylic-based, or the like. The adhesive may be of one-liquid type or two-liquid type. The adhesive is preferably an adhesive whose hardening is accelerated by heat (thermosetting adhesive), that is, a heat-trigger type (hardening is accelerated by heating such as thermal cations or thermal radicals), or contains a thermosetting polymer as a main component. In the case of a thermosetting adhesive, it is preferable because the manufacturer can control the timing of hardening. The thermosetting adhesive may be of a heat-hardening type (one that requires heating in normal use) or a room temperature hardening type (one that undergoes a hardening reaction by leaving it in normal use and does not require heating), but a room temperature hardening adhesive can be suitably used in the method according to this embodiment. Specific examples of adhesives include two-component modified silicone adhesives (modified silicone / epoxy adhesives), two-component urethane adhesives, one-component heat-curing urethane adhesives, and second-generation acrylic adhesives (SGA).

[0022] Fig. 3 shows a flow diagram of a manufacturing method of a vehicle window glass 1 with a component according to one embodiment. As shown in Fig. 3, the manufacturing method according to this embodiment includes, in this order, an arrangement step (S11) of arranging a resin component on the vehicle window glass via an adhesive, and a first curing step (S12) of locally irradiating a non-adhesive surface of the component with infrared rays to cure a local portion of the adhesive. The manufacturing method according to this embodiment may further include a second curing step (S13) of curing a main portion, which is a portion other than the local portion, after the first curing step (S12). In this specification, the first curing step (S12) may be referred to as a temporary fixing step, and the second curing step (S13) may be referred to as a main fixing step.

[0023] In this embodiment, the part 30 is temporarily fixed to the vehicle window glass 10 by hardening a local portion of the adhesive. In other words, a part of the adhesive originally used for the main fixing is used for the temporary fixing. Therefore, there is no need to prepare additional materials such as double-sided tape or other types of adhesives for the temporary fixing process. In other words, there is no increase in the number of materials for temporary fixing. Furthermore, for example, conventional temporary fixing using double-sided tape was performed manually and it was impossible or difficult to automate it on a manufacturing line, but according to this embodiment, a labor-intensive manual process is not necessary. Furthermore, even in the conventional temporary fixing using a different type of adhesive, a different type of hardening method may be required from the hardening method of the adhesive for the main fixing, but in this embodiment, such a different type of hardening method is not necessary. Therefore, temporary fixing can be performed without increasing the number of materials for temporary fixing and without increasing the labor during manufacturing, that is, in a simple process.

[0024] Next, each step of the manufacturing method according to the present embodiment will be described in more detail with reference to Fig. 3 as well as Fig. 4 to Fig. 7. Fig. 4 shows the arrangement step (S11), Fig. 5 and Fig. 6 show the first curing step (S12), and Fig. 7 shows the second curing step (S13). Fig. 6 is a schematic cross-sectional view taken along line II-II in Fig. 5.

[0025] In the arrangement step (S11), the resin part 30 is arranged on the vehicle window glass 10 via the adhesive 20. In the arrangement step (S11), the adhesive surface 31 of the part 30 is checked, and the adhesive surface 31 is cleaned as necessary. The adhesive surface 31 of the part 30 is a surface that faces the main surface of the vehicle window glass 10 and is aligned along the main surface, and may be flat or curved to match the curve of the opposing surface of the vehicle window glass 10. Next, as shown in FIG. 4, for example, the adhesive 20 is applied to a predetermined location of the adhesive surface corresponding area 31a corresponding to the adhesive surface 31 of the part 30 on the main surface of the vehicle window glass 10. The adhesive 20 can be applied by a conventionally known means according to the type of adhesive.

[0026] The adhesive 20 may be applied over the entire adhesive surface corresponding region 31a or may be applied to a part of it. Also, as shown in FIG. 4, the adhesive 20 may be applied discontinuously at multiple locations. When applied at multiple locations, the adhesive 20 may be applied in a line or dot shape. FIG. 4 shows multiple examples of linear adhesives 20 each having a substantially constant width in a plan view, but the application style of the adhesive 20 (application range, continuous or discontinuous, application area, application locations and number thereof) is determined by the configuration of the part 30, i.e., the size, shape, material type, and function of the part 30 (if it is a bracket, what is to be held, etc.). However, the adhesive 20 is applied to the location where a temporary fixing location is to be formed, i.e., the portion to be irradiated with infrared rays in the subsequent first curing step (S12), i.e., the location where a local portion of the adhesive is to be formed.

[0027] After the adhesive 20 has been applied, the component 30 is placed on the main surface of the vehicle window glass 10, with the adhesive surface 31 of the component 30 facing the adhesive surface corresponding region 31a of the vehicle window glass 10 so as to fit the adhesive surface. Note that in the placement step (S11), after the adhesive 20 has been applied to the adhesive surface 31 of the component 30, the component 30 with the adhesive 20 attached thereto may be brought into contact with a desired position on the main surface of the vehicle window glass 10. Furthermore, in cases where the component 30 has a through hole 35 (described below) formed therein, it is preferable that the adhesive 20 be applied so as to overlap the through hole 35.

[0028] After the above-mentioned arrangement step (S11), the process proceeds to a first curing step (S12). In the first curing step (S12), infrared rays are locally irradiated toward the non-adhesive surface 32 of the component 30 as shown in FIG. 5. In this specification, "locally irradiating" infrared rays means that infrared rays are irradiated to a local area and not to other areas. By locally irradiating infrared rays, only a specific part of the adhesive 20 is heated, or the specific part of the adhesive 20 is heated at a faster rate than the other parts. Therefore, when the temperature of the specific part of the adhesive 20 and the other parts are measured at the stage where the first curing step (S12) is completed, the temperature of the specific part is higher than the temperature of the main part. For such local irradiation of infrared rays, it is preferable to use a means capable of concentrating thermal energy and / or light energy locally, that is, an irradiation means with high directionality (high light collecting ability or heat collecting ability).

[0029] FIG. 5 shows an irradiation means 80 including an infrared irradiation section 81 and a power supply / control section 85 as an irradiation means for the first curing step (S12). As shown in FIG. 5, the infrared rays irradiated from the infrared irradiation section 81 of the irradiation means 80 are irradiated locally in the plan view area of ​​the entire part 30, that is, a very small part of the plan view area of ​​the entire part 30. For example, the circle equivalent diameter of the area irradiated with the infrared rays in a plan view may be 2 mm or more and 10 mm or less. That is, if the irradiation area is circular, the irradiation area may have a diameter in the above range, and if the irradiation area has a shape other than a circle, the irradiation area may have the same area as a circle having a diameter in the above range. Note that a plurality of irradiation means 80 may be prepared to perform local irradiation of infrared rays at a plurality of locations simultaneously, but the circle equivalent diameter in the above range is the value of the irradiation area in one location.

[0030] The infrared rays irradiated by the irradiation means 80 may be heat rays and / or light rays, and are not limited as long as they harden the adhesive 20, but near-infrared rays to short-wavelength infrared rays (wavelengths of 780 nm or more and 2500 nm or less) are preferred. Therefore, the irradiation means 80 may be a halogen lamp heater, for example, a halogen point heater, a laser, or the like. These irradiation means are preferred because they are non-contact and have high directionality. When a halogen point heater, a laser, or the like is used as the irradiation means 80, it has a focused light diameter (irradiation diameter) in the range of the above-mentioned circle equivalent diameter (2 mm or more and 10 mm or less).

[0031] 5, the irradiation means 80 is disposed on the side of the non-adhesive surface 32 of the component 30, and irradiates infrared rays toward the non-adhesive surface 32. The non-adhesive surface 32 is the surface of the component 30 opposite to the adhesive surface 31, and is the surface on which the adhesive 20 is not applied. The irradiation angle of the infrared rays may be perpendicular to the non-adhesive surface 32, or may be at an angle of 45° or more and 135° or less from the perpendicular direction. However, irradiation perpendicular to the non-adhesive surface 32 allows localized heating and hardening of the adhesive 20 more efficiently.

[0032] When infrared rays are irradiated toward the non-adhesive surface 32, the infrared rays may be directly irradiated to the non-adhesive surface 32 of the component 30, or may not be directly irradiated to the component 30, for example, when the component 30 has a through hole 35. The through hole 35 is a hole penetrating the component 30 in the thickness direction, as shown in Figs. 4 and 5. When the component 30 has a through hole 35, the infrared rays from the infrared irradiating unit 81 can be directly irradiated to the surface of the adhesive 20 through the through hole 35, as shown in Figs. 5 and 6. That is, the infrared rays can be irradiated to the area of ​​the adhesive 20 exposed through the through hole 35 of the component 30. Note that even in this case, the infrared rays may be directly irradiated to the resin around the through hole 35 as well as the surface of the adhesive 20.

[0033] The infrared irradiation in the first curing step (S12) rapidly cures a local part of the adhesive 20 by applying a large amount of energy in a short time, and therefore the resin part directly irradiated with the infrared rays or the resin in the vicinity of the infrared irradiation area may undergo denaturation that is visible by a normal method. Therefore, as described above, by providing the through-hole 35 (FIGS. 4 to 6) in advance in the part 30, the resin part directly irradiated with the infrared rays can be reduced or eliminated, and the resin part 30 can be reduced in the denatured part. In addition, by passing the infrared rays through the through-hole 35, the adhesive 20 can be directly irradiated with the infrared rays (FIG. 6), and the adhesive 20 can be efficiently locally cured in the first curing step (S12). In this specification, the denaturation of the resin part 30 by the infrared irradiation includes physical deformation (bubble formation, change in surface roughness, formation of concave or convex parts on the surface) and / or change in chemical composition (charring, oxidation, decomposition, discoloration, etc.).

[0034] The size of the through hole 35 can be determined depending on the size of the local portion (temporarily fixed portion) to be cured in the first curing step (S12), the type of resin material of the resin part 30, the purpose and function of the part 30, etc., but the through hole 35 may be, for example, a circular hole with a diameter in plan view of preferably 2 mm to 10 mm, more preferably 4 mm to 8 mm, or a hole with a size having an area in plan view equivalent to that of the circle. By having the through hole 35 within the above range, infrared rays can be sufficiently transmitted to reduce the portion of the resin part 30 that is denatured, the adhesive 20 can be cured efficiently, and the robustness of the part 30 itself is also ensured.

[0035] From the viewpoint of reducing the portion of the resin directly irradiated with infrared rays and reducing the denaturation of the resin part 30, the part 30 does not necessarily have to be formed with the through hole 35, but may be a portion where the resin material is removed in the thickness direction compared to the surroundings (thickness direction material removed portion). For example, instead of the through hole 35, a notch formed by cutting the periphery of the part 30 in the surface direction (i.e., a recess formed by recessing the periphery of the part 30 in a plan view), or a thin part where the thickness of the part 30 is thinner than the surroundings, may be provided in the part 30. However, since infrared rays can be directly irradiated to the adhesive 20, it is preferable to provide the through hole 35 or the notch in the part 30. In addition, since the temporary fixing of the part 30 is more effective in connecting the part 30 to the vehicle window glass 10 when the part 30 is temporarily fixed at a position away from the periphery, it is preferable that the thickness direction material removed portion is the through hole 35 or the thin part rather than the notch.

[0036] If the part 30 itself originally has thickness-wise material removed portions, such as through holes, notches, thin sections, etc., formed for another purpose, then such originally formed portions may be utilized when irradiating with infrared rays.

[0037] As described above, when the component 30 has a thickness-direction material-removed portion, when the component 30 is placed on the vehicle window glass 10 via the adhesive 20 in the above-mentioned placement step (S11), it is preferable to adjust the position of the component 30 so that at least a part of the thickness-direction material-removed portion overlaps the adhesive 20, and it is more preferable to adjust the position so that the entire thickness-direction material-removed portion overlaps the adhesive 20, that is, is included in the application area of ​​the adhesive 20 in a plan view. For example, in the example shown in Fig. 4, the adhesive 20 is applied to a position where the through hole 35 is to be placed. As a result, at the stage where the placement step (S11) is completed, the adhesive 20 is visible through the through hole 35 when the component 30 is viewed from the non-adhesive surface 32.

[0038] Then, in the first curing step (S12), infrared rays are irradiated toward the thickness-wise material removed portion of the component 30, preferably toward the center of the thickness-wise material removed portion. For example, when using a component 30 having a through hole 35 formed therein and a halogen spot heater as the curing means in the first curing step (S12), it is preferable to perform irradiation so that the center of the through hole 35 in a plan view (the centroid if the through hole 35 is not circular) coincides with the center of the focal circle of the halogen spot heater (FIG. 6).

[0039] In one embodiment, a part 30 in which no thickness direction material removed portion as described above is formed may be used. In other words, infrared rays may be irradiated to the part 30 without any processing. In this case, the infrared rays are directly irradiated to the resin part 30, so that the irradiated portion of the resin part 30 may be deformed.

[0040] Thus, in the first curing step (S12), a small portion of the adhesive 20 is heated by localized irradiation with infrared rays, and cured first. The local portion cured in this manner becomes a temporary fastening portion between the component 30 and the vehicle window glass 10. The temporary fastening portion can prevent misalignment between the component 30 and the vehicle window glass 10, for example, even if vibration occurs on a production line in a subsequent step. When the first curing step (S12) is completed, the hardness of the specified portion of the adhesive 20 is greater than the hardness of the portion other than the specified portion (main portion).

[0041] The local portion cured in the first curing step (S12) may not be one location, but may be a plurality of separate locations. When multiple local portions of the adhesive 20 are to be cured, infrared radiation may be irradiated to a plurality of locations. The size, number, and position of the local portions can be appropriately determined depending on the shape and size of the component 30, the area and shape of the adhesive surface 31, the amount of adhesive 20 applied, and the like. The area of ​​the local portion of the adhesive (the total area when multiple local portions are formed) may be preferably 0.5% to 20%, and preferably 3% to 15%, of the total area of ​​the adhesive applied in the arrangement step (S11). By setting the amount of the local portion of the adhesive to be within the upper range, the first curing step (S12) can be performed as quickly as possible, and a sufficient amount of adhesive cured in the second curing step (S13) described later can be secured, so that sufficient adhesive strength can be obtained between the component 30 and the vehicle window glass 10.

[0042] In the first curing step (S12), the output of infrared radiation for curing one local portion of the adhesive 20 may be preferably 20 W or more and 100 W or less. When the irradiation means 80 is a near-infrared or short-wavelength infrared heater, the distance (or focal length) from the opening of the heater to the irradiated surface may be 6 mm or more and 12 mm or less. In addition, in the first curing step (S12), the time for curing one local portion of the adhesive (curing time) may be preferably 70 seconds or less, more preferably 60 seconds or less. In addition, the curing time may be 30 seconds or more. In the case where the vehicle window glass 10 is a laminated glass, the condition of the infrared radiation in the first curing step (S12) is a condition that the intermediate film 15 in the laminated glass is not altered (foaming, discoloration, deformation, etc.). Therefore, even if the temperature of the intermediate film 15 of the laminated glass is measured in the first curing step (S12), the temperature is kept at 100° C. or less, preferably 80° C. or less, more preferably 50° C. or less, and even more preferably 30° C. or less.

[0043] In this specification, the curing of the adhesive refers to the adhesive solidifying and reaching an equilibrium or nearly equilibrium state. The temperature of the adhesive is measured when irradiated with infrared rays, and the time until the temperature reaches a target temperature, i.e., the target curing temperature (target curing value) and gels can be used as a guide for the completion of curing. The target curing temperature can be determined for each adhesive used. For example, the gelling time of a given adhesive at multiple temperatures can be measured, and the highest gelling temperature within the temperature range at which the adhesive 20 is not damaged can be set as the target curing temperature. The gelling time can be measured by a method conforming to the gelling time method A in JIS K 6910:2007. The target curing temperature of the adhesive is a temperature higher than room temperature (15 to 25°C), and can be, for example, 40°C or higher and 100°C or lower.

[0044] After the first curing step (S12), the process proceeds to a second curing step (S13). In the second curing step (S13), a main portion of the adhesive 20 other than the local portion cured in the first curing step (S12) is cured. This causes the entire adhesive 20 to harden, and the entire component 30 is bonded to the vehicle window glass 10 via the adhesive 20, so that a vehicle window glass 1 with a component (FIG. 1) can be obtained.

[0045] The specific method of the second curing step (S13) is not particularly limited. For example, a known method such as leaving the adhesive until the main part of the adhesive is cured may be used. When the main part of the adhesive is cured by leaving the adhesive, the leaving environment, specifically the temperature and / or humidity, can be appropriately adjusted.

[0046] Also, in the second curing step (S13), the curing can be promoted by increasing the temperature of the main part of the adhesive 20. For example, irradiation of near-infrared rays to short-wavelength infrared rays, such as a halogen lamp heater (such as a halogen wide heater, a halogen point heater, or a halogen line heater), a laser, induction heating, an oven, or hot air, may be used to cure the main part of the adhesive 20 in the second curing step (S13). Therefore, a halogen heater may be used in the first curing step (S12) and the second curing step (S13), and the irradiation conditions may be changed in both steps. As a result, it is sufficient to install one device throughout the first curing step (S12) and the second curing step (S13), and there is no need to prepare separate devices for the two steps, which simplifies the manufacturing equipment and reduces the manufacturing effort.

[0047] Regardless of which method is used in the second curing step (S13), the curing time required for the first curing step (S12) is shorter than the curing time required for the second curing step (S13). The ratio (T1 / T2) of the curing time (T1) required for the first curing step (S12) to the curing time (T2) required for the second curing step (S13) may be 0.2 or more and 0.8 or less. However, the curing time per unit amount of adhesive in the first curing step (S12) is longer than the curing time per unit amount of adhesive in the second curing step (S13), and the adhesive is heated and cured efficiently in a short time in the first curing step. Note that the unit amount of adhesive refers to the unit mass or unit volume of the adhesive.

[0048] When the second curing step (S13) is performed by irradiating infrared rays to cure the main portion of the adhesive 20, for example, a heat absorbing layer may be provided on the main surface (the surface facing the component 30) of the vehicle window glass 10, and the heat absorbing layer or its vicinity may be locally heated to transfer the heat to the adhesive 20, thereby raising the temperature of the main portion of the adhesive 20. This makes it possible to prevent the intermediate film arranged in the laminated glass from being altered in the second curing step (S13), even when a laminated glass is used as the vehicle window glass 10. The heat absorbing layer may be any layer made of a material that can absorb heat and transmit the absorbed heat, or absorb energy supplied from the outside (for example, light energy such as heat rays) and convert the absorbed energy into heat to obtain heat. For example, since the shielding layer 50 (FIG. 1) formed on the peripheral portion of the vehicle window glass 10 described above is a heat absorbing layer, the shielding layer 50 can be irradiated with heat rays and / or light rays in the second curing step (S13) to cure the main portion (remaining portion) of the adhesive 20. As shown in FIG. 7, the infrared ray irradiating means 81a of the irradiating means 80a can be disposed above the shielding layer 50 to directly irradiate the shielding layer 50 with infrared rays. In this case, the output of the infrared ray irradiating section 81a in the second curing step (S13) may be 40 W or more and 80 W or less. In addition, the distance (or focal length) from the opening of the heater to the surface of the heat absorbing layer (shielding layer 50) may be 10 mm or more and 30 mm or less.

[0049] When both the first curing step (S12, temporary fixing) and the second curing step (S13, final fixing) are performed by irradiating infrared rays, the first curing step (S12) is performed under conditions where the temperature rise rate per unit amount of adhesive is higher than the temperature rise rate per unit amount of adhesive in the second curing step (S13).

[0050] When the vehicle window glass 10 is a laminated glass, the second curing step (S13) is also performed so as not to cause denaturation (foaming, discoloration, deformation, etc.) of the interlayer film included in the laminated glass. For example, the heating in this embodiment is performed so that the temperature of the interlayer film is 100°C or less, preferably 80°C or less, more preferably 50°C or less, and further preferably 30°C or less.

[0051] One embodiment of the present invention may be a vehicle window glass with a resin part (FIG. 1) manufactured by the above-mentioned manufacturing method. Specifically, the vehicle window glass with a resin part is manufactured by a method including a disposing step of disposing a resin part on a vehicle window glass via an adhesive, and a first curing step of locally irradiating a non-adhesive surface of the resin part with infrared rays to cure a local portion of the adhesive.

[0052] In one embodiment, a vehicle window glass with a component is provided, in which a resin component is fixed to the vehicle window glass via an adhesive, and the adhesive has a local portion and a main portion other than the local portion, and the adhesive strength per unit area between the resin component and the vehicle window glass via the local portion may be smaller than the adhesive strength per unit area between the resin component and the vehicle window glass via the main portion. For example, a ratio (S1 / S2) of the adhesive strength (S1) at the local portion to the adhesive strength (S2) at the main portion may be 0.05 or more and 0.3 or less. The resin component is locally modified by irradiation with infrared rays, and the modified portion faces the local portion. The modification may be the above-mentioned physical modification or chemical modification, or both.

[0053] The localized portion of the adhesive has a circle-equivalent diameter of 2 mm to 10 mm. The area of ​​the localized portion in plan view (the total area when multiple localized portions are formed) may be preferably 0.5% to 20%, and more preferably 3% to 15%, of the total area of ​​the adhesive used.

[0054] In one embodiment, the adhesive has a local portion and a main portion other than the local portion, and the hardness of the local portion is lower than the hardness of the main portion. The density of the local portion of the adhesive is lower than the density of the main portion. Furthermore, when observing air bubbles contained in the adhesive in a vehicle window glass with a resin part, the total volume of air bubbles per unit volume contained in the local portion is larger than the total volume of air bubbles per unit volume in the main portion. The main portion may contain no or almost no air bubbles.

[0055] In the above-mentioned vehicle window glass with a resin part, one type of adhesive may be interposed between the resin part and the vehicle window glass. The vehicle window glass with a resin part may include a double-sided tape used for temporary fixing, but is preferably a double-sided tape-less structure that does not include a double-sided tape.

[0056] Furthermore, the resin part 30 may have a thickness direction material removal portion (through hole, notch, or thin part) where a part or all of the material has been removed in the thickness direction. The above-mentioned part of the resin part 30 where the material has been modified may overlap with the thickness direction material removal portion and / or its surroundings. For example, when the resin part 30 has a through hole 35 (FIG. 5, etc.) or a notch, the modification may be visible around the through hole 35 or the notch. When the resin part 30 has a thin part, a part or the whole of the thin part, and in some cases, the surroundings thereof, are modified. EXAMPLES

[0057] Hereinafter, the embodiments of the present invention will be described in more detail based on experimental examples. In these examples, components were attached to the main surface of glass via an adhesive under various conditions, and automotive window glass with components was produced and evaluated. Examples 1 to 6 are examples, and Examples 7 to 11 are comparative examples.

[0058] Each example was evaluated as follows: <Process applicability evaluation> (Time until temporary fastening) The time required for temporary bonding was evaluated. When temporary bonding was achieved by locally heating the adhesive, the time required for the local area of ​​the adhesive to reach the target curing temperature and gel was recorded. The evaluation criteria were as follows: 〇: 70 seconds or less ×: More than 70 seconds The target curing temperature is the desired temperature that the adhesive heated in the curing process should reach. In this example, in order to determine the target curing temperature, the gelation time was measured for each adhesive used at multiple temperatures, and the highest gelation temperature within the temperature range that does not damage the adhesive or the adherend was set as the target curing value. The gelation time was measured using a method that conforms to the gelation time method A in JIS K 6910:2007.

[0059] (Additional material for temporary fastening) The materials required for temporary fixing were evaluated as follows: ○: No additional materials were required ×: Additional materials were required Table 1 also lists the scores for additional materials in parentheses.

[0060] (Time required for tasks that are difficult to automate) We evaluated whether any tasks that are difficult to automate were required. If such tasks were not required, we marked them as "unnecessary," and if they were required, we marked them as "necessary." For example, the double-sided tape used in Example 7 must be applied manually with current technology, and it is virtually impossible to automate the application process, so we marked it as "necessary."

[0061] (Whether or not adhesive thickness can be controlled) We evaluated whether the adhesive thickness (the distance between the bracket and the laminated glass) in the bracket-attached laminated glass could be controlled. In Table 1, cases where it could be controlled or adjusted during the manufacturing process are marked "possible," and cases where it could not be controlled are marked "not possible."

[0062] <Quality evaluation> (Glass temperature rise) The temperature of the glass plate was continuously measured throughout the entire black ceramic surface near the bracket attachment position from the start to the end of the production of the component-attached glass, that is, through the placement process, temporary fixing process, and final fixing process, and the maximum temperature rise (°C) was calculated. max The temperature of the glass plate before the temporary fixing (first curing) is t0, the maximum temperature of the glass plate is t1, and t1- t0The evaluation criteria were as follows: ○: The maximum temperature rise was 30°C or more. ×: The maximum temperature increase was more than 30°C.

[0063] (Strength immediately after temporary fastening) The shear strength of the laminated glass with the parts obtained was measured within 5 seconds after temporary fixing (first curing). The shear strength was measured by hooking a tensile tester (Imada, ZTS-500N) near the opening of the bracket and pulling at 50 mm / min. The strength value indicated when breakage occurred was recorded. The evaluation criteria were as follows: ◯: The strength at break was 30N or more. ×: The strength value at break was less than 30N.

[0064] (Example 1) = Placement Steps = A laminated glass sample (100 mm x 100 mm) was prepared by bonding two glass plates with a thickness of 2 mm together via a polyvinyl butyral interlayer (0.73 mm). A shielding layer made of a fired ceramic paste was formed on one of the main surfaces of the laminated glass sample. On the other hand, a polybutylene terephthalate (PBT) sensor bracket (total length 70 mm, width 50 mm, adhesive surface area approximately 2000 mm) was 2 A bracket (having a hexagonal shape with a roughly circular opening for mounting the sensor, the same shape as the bracket shown in Fig. 4) was prepared. The bracket had one through-hole with a diameter of 6 mm (Fig. 4).

[0065] Next, within the range where the shielding layer was formed on the main surface of the laminated glass sample, a bonding surface corresponding area corresponding to the bonding surface of the bracket to be placed was set. A total of 3.6 g of two-liquid modified silicone / epoxy adhesive ("MOS400" manufactured by Konishi Co., Ltd.) was applied to three separate locations within the bonding surface corresponding area of ​​the laminated glass sample, at the same locations as those shown in FIG. 5. Then, the bonding surface of the bracket was placed so as to correspond to the bonding surface corresponding area set on the laminated glass sample. After placing the bracket on the laminated glass in this way, it was confirmed that the through hole of the bracket overlapped with the adhesive (the adhesive was visible through the through hole of the bracket) when viewed from the bracket side. The distance between the bracket and the laminated glass sample (the thickness of the sandwiched adhesive) was adjusted to be about 1 mm.

[0066] =Temporary Fixing (First Curing)= A short-wavelength infrared heater (halogen point heater, "HSH-18" manufactured by Fintech Co., Ltd.) was used to irradiate light from above the position where the through-hole was provided. Specifically, the heater was fixed in a position where its focal point coincided with the center of the through-hole in a plan view and the distance from the heater opening to the adhesive surface was about 9 mm (focal length was about 9 mm), and irradiation was performed at an output of 70 W. Irradiation was continued until the temperature of the irradiated adhesive part (local part) reached the target hardening temperature of the adhesive used in each example and gelled.

[0067] =Final fixing (second curing)= An apparatus equipped with a halogen line heater (near-infrared heater, Fintech's "LHW-30") with a mirror length of 84 mm was placed facing the shielding layer of the laminated glass, with the focal point located approximately 5 mm away from the bracket in the direction of the surface of the laminated glass, and the distance from the heater opening to the shielding layer surface being approximately 5 mm (focal length approximately 5 mm), and infrared rays were irradiated at an output of 300 W. Irradiation was continued until the temperature of the parts (main parts) other than the local parts hardened in the temporary fixing process reached the target hardening temperature of the adhesive used and gelled.

[0068] (Example 2) A bracket-attached laminated glass was obtained in the same manner as in Example 1 (the size and shape of the bracket were also the same as in Example 1), except that the bracket was changed to one made of polyamide (PA).

[0069] (Example 3) A bracket-attached laminated glass was obtained in the same manner as in Example 1 (the size and shape of the bracket were also the same as in Example 1), except that the bracket was changed to one made of polycarbonate (PC).

[0070] (Example 4) The sensor bracket (total length 74 mm, width 3.8 mm, adhesive surface area 320 mm) is made mainly of iron, but has an epoxy resin coating formed on the surface by cathodic electrochemical coating. 2 ) was used to obtain a bracket-attached laminated glass in the same manner as in Example 1. In the arrangement step, a total of 0.6 g of a two-liquid modified silicone / epoxy adhesive ("MOS400" manufactured by Konishi Co., Ltd.) was applied to three locations in the area corresponding to the adhesive surface on the laminated glass sample, and the distance between the bracket and the laminated glass sample (the thickness of the adhesive sandwiched) was adjusted to 1.2 mm. In addition, the sensor bracket used in this example also had a through hole with a diameter of 6 mm formed therein, and when the bracket was arranged, the through hole was made to overlap with the adhesive, and the light irradiation by the heater in the temporary fixing (first curing) was also performed under the same conditions as in Example 1, with the focal point coinciding with the center of the through hole in a plan view.

[0071] (Example 5) A bracket-attached laminated glass was obtained in the same manner as in Example 1, except that the entire adhesive was changed to a two-component urethane adhesive (WS222 / B1, manufactured by Sika Hamatite Co., Ltd.).

[0072] (Example 6) A bracket-attached laminated glass was obtained in the same manner as in Example 1, except that the entire adhesive was replaced with a one-component heat-curing urethane adhesive (Sunstar Corporation's "Penguin Cement #8800") and a primer (Sunstar Corporation's "SC-241") was applied to the bonding surface of the glass before applying the adhesive.

[0073] (Example 7) Instead of temporarily fixing by hardening a localized portion of the applied adhesive, double-sided tape was used as a temporary fixing method. Specifically, a two-part modified silicone / epoxy adhesive ("MOS400" manufactured by Konishi Co., Ltd.) was applied in the same manner as in Example 1 to the area corresponding to the adhesive surface set on the main surface of the laminated glass, and then double-sided tape was applied in a position in the area corresponding to the adhesive surface that did not overlap with the applied position of the adhesive, and the bracket was positioned so that the adhesive surface of the bracket corresponded to the area corresponding to the adhesive surface. In other respects, a bracket-attached laminated glass was obtained in the same manner as in Example 1. The distance between the bracket and the laminated glass sample was equal to the thickness of the double-sided tape (1.2 mm).

[0074] (Example 8) Instead of temporarily fixing the glass by hardening localized areas of the applied adhesive, an instant adhesive was used as a temporary fixing method. Specifically, a two-part modified silicone / epoxy adhesive (Konishi's "MOS400") was applied to the area corresponding to the adhesive surface set on the main surface of the laminated glass, and then an instant adhesive (Cemedine's "Aron Alpha EXTRA") was applied so as not to overlap with the adhesive in the area corresponding to the adhesive surface, and the bracket was positioned so that its adhesive surface corresponded to the area corresponding to the adhesive surface. In all other respects, the bracket-attached laminated glass was obtained in the same manner as in Example 1. The instant adhesive was not hardened if there was a gap between the bracket and the laminated glass sample, so it was produced without any gaps.

[0075] (Example 9) The bracket was placed on the laminated glass sample via adhesive, and then left for 168 hours in an environment of room temperature (23±3°C) and humidity of 50-70%. In other words, without temporary fixing (first curing), the bracket was left at room temperature for permanent fixation (second curing).

[0076] (Example 10) Instead of the short-wavelength infrared heater used in Example 1, an oven (PV-222 manufactured by ESPEC) was used for temporary fixing (first curing), but localized curing was not possible and the entire adhesive reached the target curing temperature. As a result, only the permanent fixing (second curing) was performed using an oven without temporary fixing (first curing).

[0077] (Example 11) Instead of the short-wave infrared heater used for the temporary fixing (first curing), a hot air heater (Fintech's "SAHD-15S") was used to attempt temporary fixing (first curing), but localized curing was not possible and the entire adhesive reached the target curing temperature (described below). As a result, only the permanent fixing (second curing) was performed using the hot air heater without the temporary fixing (first curing).

[0078] [Table 1]

[0079] As shown in Table 1, in Examples 1 to 7 in which temporary bonding was achieved by hardening localized portions of the adhesive, it was found that no additional material was required for temporary bonding, and temporary bonding could be achieved with little effort.

[0080] Although the present invention has been described above based on the embodiments and examples, the present invention is not limited to these embodiments and examples. Furthermore, the above embodiments can be changed, modified, substituted, added, deleted, and combined in various ways within the scope of the claims, and these also fall within the technical scope of the present invention. [Explanation of symbols]

[0081] 1 Vehicle window glass with parts 10 Vehicle window glass 11, 12 Glass plate 15 Interlayer 20. Glue 30 Plastic parts 31 Adhesive surface of resin parts 32 Non-adhesive surface of resin parts 35 Through hole (material reduction area in thickness direction) 50 shielding layer 80, 80a irradiation means 81, 81a Infrared irradiation unit 85, 85a Power supply and control unit

Claims

1. A process of placing a resin part on a vehicle window glass via an adhesive; and a first curing step of locally irradiating infrared rays toward a non-adhesive surface of the resin part to cure a local portion of the adhesive.

2. The method further includes a second curing step of curing a main portion of the adhesive other than the local portion, 2. The method for manufacturing a vehicle window glass with a resin part according to claim 1, wherein a curing time per unit amount of adhesive in the first curing step is longer than a curing time per unit amount of adhesive in the second curing step.

3. The method for manufacturing a window glass for a vehicle with a resin part according to claim 1 or 2, wherein an irradiation diameter of the infrared ray is 2 mm or more and 10 mm or less.

4. The method for producing a window glass for a vehicle with a resin part according to claim 3 , wherein the infrared rays are near-infrared rays.

5. 3. The method for manufacturing a vehicle window glass with a resin part according to claim 1, wherein an amount of the local portion hardened in the first hardening step is 0.5% or more and 20% or less of a total amount of the adhesive.

6. The method for producing a window glass for a vehicle with a resin part according to claim 1 or 2, wherein the resin part is modified by the irradiation.

7. a thickness direction material removed portion is formed in the resin part, the thickness direction material removed portion being a portion in which a part or all of the material is removed in the thickness direction; The method for producing a vehicle window glass with a resin part according to claim 6 , wherein the modification occurs by irradiating the thickness-direction material removal portion with the infrared ray.

8. The method for producing a vehicle window glass with a resin part according to claim 1 or 2, wherein the resin part is a mounting part for an in-vehicle device.

9. A vehicle window glass with a component, the vehicle window glass being formed by fixing a resin component to the vehicle window glass via an adhesive, the adhesive has a local portion and a main portion other than the local portion, an adhesive strength per unit area between the resin part and the vehicle window glass via the local portion is smaller than an adhesive strength per unit area between the resin part and the vehicle window glass via the main portion; The resin part is locally denatured by irradiation with infrared rays, The modified portion faces the local portion.

10. The vehicle window glass with a resin part according to claim 9 , wherein an equivalent circle diameter of the local portion is 2 mm or more and 10 mm or less in a plan view.

11. a thickness direction material removed portion is formed in the resin part, the thickness direction material removed portion being a portion in which a part or all of the material is removed in the thickness direction; The vehicle window glass with a resin part according to claim 10 , wherein the modified portion overlaps the thickness-direction material-removed portion and / or a peripheral portion thereof.

12. The vehicle window glass with a resin part according to claim 9 or 10, wherein the resin part is a mounting part for an in-vehicle device.

Citation Information

Patent Citations

  • Module and method for manufacturing the same

    JP2022007591A